PENGAMAN GANDA SEPEDA MOTOR DENGAN SISTEM SMART SECURITY - darwis Parawiro; andi asni b; Aswadul Fitri Saiful Rahman (Lembaga Penelitian Universitas Balikpapan, 2019)
The dual safety system is designed to protect scooter from theft when a motorcycle is placed in place nothing supervision from its owner. There are two types of safety device for scooter, they are electric and nonelectric. One of the most widely used examples of this two safety device is using an electric alarm and a nonelectric using a steering lock. However, in the two examples of safety devices that cannot be relied upon if the Scooter is in a place that is less supervision, it is certain that the owner cannot monitor it. So the purpose of the safety device Arduino-based dual safety device is designed to effectively secure Scooter because it is equipped with GPS that is used to track the location of scooter coordinates without distance being limited.The device is equipped with a GSM module as communication between the owner and the safety device so that the owner can monitor his Scooter remotely, using SMS. If the SMS is sent to the mobile number installed on the GSM module with the appropriate SMS command, the tool will work according to the SMS command.